2018
DOI: 10.1182/blood-2017-12-823757
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human phase 1 clinical study of the IL-15 superagonist complex ALT-803 to treat relapse after transplantation

Abstract: New therapies for patients with hematologic malignancies who relapse after allogeneic hematopoietic cell transplantation (allo-HCT) are needed. Interleukin 15 (IL-15) is a cytokine that stimulates CD8 T-cell and natural killer (NK) cell antitumor responses, and we hypothesized this cytokine may augment antileukemia/antilymphoma immunity in vivo. To test this, we performed a first-in-human multicenter phase 1 trial of the IL-15 superagonist complex ALT-803 in patients who relapsed >60 days after allo-HCT. ALT-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
286
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 335 publications
(296 citation statements)
references
References 36 publications
8
286
0
2
Order By: Relevance
“…ALT-803 (IL-15 mutant/IL-15Rα/Ig1fusion protein) was administered i.v. or s.c. to 33 patients with hematological malignancies once weekly for four doses (Romee et al, 2018), and pharmacokinetic analysis revealed prolonged serum concentrations following s.c. compared with i.v. infusion.…”
Section: Il-15 In Autoimmune Diseasesmentioning
confidence: 99%
“…ALT-803 (IL-15 mutant/IL-15Rα/Ig1fusion protein) was administered i.v. or s.c. to 33 patients with hematological malignancies once weekly for four doses (Romee et al, 2018), and pharmacokinetic analysis revealed prolonged serum concentrations following s.c. compared with i.v. infusion.…”
Section: Il-15 In Autoimmune Diseasesmentioning
confidence: 99%
“…20 Lastly, immune modulation post-HCT could diminish relapse risk. Based on recently published data highlighting successful IL-15 superagonist (ALT-803) induced NK cell and CD8+ T cell expansion in patients relapsing post allogeneic transplant, 21 we are now utilizing ALT-803 prophylaxis post RIC allogeneic transplant for patients with AML and MDS in attempts to minimize relapse risk. Combining pre-transplant disease status specific requirements, personalized conditioning intensity approaches, and post-HCT maintenance pathways for high relapse risk diseases will improve long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…62 Several studies targeting NKG2A in order to enhance NK and CD8+ T cell functions using the NKG2A blocking antibody, Monalizumab, are now underway for cancer therapy. 63,64 Anti-NKG2A antibody treatment has also been shown to improve NK cell cytotoxicity and viral clearance in and Romee et al 71 ). Further, ALT-803 is being tested in concert with other checkpoint inhibitors such as anti-PD-1 therapy in patients with metastatic nonsmall cell lung cancer.…”
Section: Blocking Inhibitory Nk Cell Receptors During Infectionmentioning
confidence: 99%
“…ALT‐803 (now N803) is a fusion complex of IL‐15 and IL‐15Rα with IgG1 Fc that has enhanced IL‐15 biologic activity through a single amino acid mutation in IL‐15 . ALT‐803 has been shown to be well tolerated in patients with relapsed hematologic malignancies with augmented NK and T cell responses (ClinicalTrials.gov ID: NCT01885897 and Romee et al …”
Section: Introductionmentioning
confidence: 99%